WAYS TO IMPROVE THE QUALITY AND EFFICIENCY OF THE EDUCATIONAL SYSTEM - Mustafakulov, Asatulla; Usanov, Ulugbek (Science technology&Digital finance, 2023)
There are enlightened some issues of increasing of management in the sphere of higher educational institutions and improving of preparation of compete able personal as educates of different spheres are increasing and widening of study demand by appearing of new specialists.